Heat Mapping and Plastic Strain Radius Modeling of Dual-Tool Friction Stir Welds 6061 Aluminum Alloy Plate Using FEM - Rikko Putra Youlia; Diah Utami; Dedik Romahadi; Tang Yishuang (Universitas Mercu Buana, 2024)
This study investigates the effects of Dual-Tool Friction Stir Welding (DT-FSW) parameters on the weld quality of 8 mm thick 6061 aluminum alloy plates, specifically focusing on the elimination or minimization of the